(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: smoking is a very important public health problem, urgently requiring immediate and effective measures due to its harmful effect on health. The purpose of this study was to collect baseline information about the magnitude of smoking problem, knowledge, attitude, and practice among family members of primary school students in the northwest region of Iran. Methods: of 55 680 primary school students (the 3th, 4th and 5th grades), 7.1% (n=3 954) were selected using randomized multi-stage cluster sampling. Data collection was conducted in April, May, and June 2011, by means of a self-administered two-page questionnaire. Results: a total of 3 954 students (57.6% boys and 42.3% girls) with the mean age of 10.46±1.09 years were evaluated. According to our data, the prevalence of cigarette smoking among fathers was more than other family members (27.1% versus 17.8%) whereas the prevalence of water pipe smoking among fathers and other family members was almost similar (9.2% and 9.7% respectively). None of the smoking type was prevalent among mothers (cigarette: 1% and water pipe: 1.1%). Considerable numbers of all students under study had been exposed to secondhand smoke at home (cigarette: 19.8% and water pipe: 7.7%). Conclusions: considering our findings, two procedures recommended to prevail the problem are to provide greater education about hazards of tobacco consumption among students and their family; and to legislate new laws by officials to ban tobacco use at home.